2022
DOI: 10.1038/s41467-022-34961-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cross-neutralizing antibodies by a permuted hepatitis C virus glycoprotein nanoparticle vaccine candidate

Abstract: Hepatitis C virus (HCV) infection affects approximately 58 million people and causes ~300,000 deaths yearly. The only target for HCV neutralizing antibodies is the highly sequence diverse E1E2 glycoprotein. Eliciting broadly neutralizing antibodies that recognize conserved cross-neutralizing epitopes is important for an effective HCV vaccine. However, most recombinant HCV glycoprotein vaccines, which usually include only E2, induce only weak neutralizing antibody responses. Here, we describe recombinant solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 110 publications
0
26
0
Order By: Relevance
“…Another potential avenue of exploration with E1E2 NPs is the potential to create mosaic and cocktail mixtures as a means to enhance neutralisation breadth as in the E2E1 NP study. 155 It is not clear, nor has it been systematically investigated, whether the best choice for an HCV vaccine will be a single patient-derived strain derived from an elite neutraliser or a mixture of representative strains from multiple genotypes, perhaps varying based on the geographical distribution of genotypes and population to be vaccinated. The successful development of mosaic NP vaccine candidates against SARS-CoV-2 148 suggests that once a NP-based E1E2 vaccine system is established, the mosaic versus single-strain immunogen design can be more thoroughly investigated.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Another potential avenue of exploration with E1E2 NPs is the potential to create mosaic and cocktail mixtures as a means to enhance neutralisation breadth as in the E2E1 NP study. 155 It is not clear, nor has it been systematically investigated, whether the best choice for an HCV vaccine will be a single patient-derived strain derived from an elite neutraliser or a mixture of representative strains from multiple genotypes, perhaps varying based on the geographical distribution of genotypes and population to be vaccinated. The successful development of mosaic NP vaccine candidates against SARS-CoV-2 148 suggests that once a NP-based E1E2 vaccine system is established, the mosaic versus single-strain immunogen design can be more thoroughly investigated.…”
Section: F I G U R Ementioning
confidence: 99%
“…The third NP study 155 utilised a permuted version of E1E2 in which the order of the antigens in the open reading frame was reversed (i.e. E2E1) and the I53‐50 platform for NP display.…”
Section: Proof‐of‐principle Np Studies For Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…Computationally designed polyhedral assemblies displaying antigens are promising vaccine candidates, triggering robust immune responses. [103][104][105][106][107][108][109][110][111][112][113][114][115][116] Indeed several candidates have advanced to clinical trials, [116][117][118] and more recently a nanoparticle vaccine for COVID-19 has demonstrated the safety and immunogenicity of this technology platform in a phase 1/2 clinical trial, achieving approval for use in South Korea. [119] These protein assemblies have also been used as fluorescence standards, through the display of a defined number of green fluorescent protein molecules, [40,120] and as scaffolds for cryogenic electron microscopy (cryo-EM), through the rigid helical fusion of specific DARPin domains, enabling the analysis of proteins that would otherwise be too small to achieve near-atomic resolution.…”
Section: Current Applications Prevailing Challenges and Rising Opport...mentioning
confidence: 99%
“…First, the exterior surface of the designed polyhedral assemblies can be decorated with a variety of molecules through genetic fusion. Computationally designed polyhedral assemblies displaying antigens are promising vaccine candidates, triggering robust immune responses [103–116] . Indeed several candidates have advanced to clinical trials, [116–118] and more recently a nanoparticle vaccine for COVID‐19 has demonstrated the safety and immunogenicity of this technology platform in a phase 1/2 clinical trial, achieving approval for use in South Korea [119] .…”
Section: Current Applications Prevailing Challenges and Rising Opport...mentioning
confidence: 99%